Integrating Indigenous Socio-Cultural Values into GIS–AHP-Based Customary Forest Zoning - Arif Hidayat; Adam Malik; Hamzari; Misrah (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2026)
Customary forests play an important role in maintaining ecological functions, cultural values, and local livelihoods. However, most forest zoning studies based on Geographic Information Systems (GIS) and the Analytical Hierarchy Process (AHP) primarily emphasize biophysical parameters and rarely integrate indigenous socio-cultural values as spatial decision-making criteria. This limitation is particularly relevant in customary forest areas, where traditional norms and sacred sites strongly influence land-use practices and resource management. Therefore, this study aimed to analyze the biophysical and socio-cultural factors influencing forest management and to develop a management zoning system for the Suaka Katuwua To Lindu Customary Forest using an integrated GIS–AHP approach. The study employed nine parameters, namely slope, elevation, land cover, distance from rivers, soil type, rainfall, distance from roads, distance from settlements, and sacred areas. Biophysical data were obtained from DEMNAS, Landsat 8 imagery, RBI BIG maps, CHIRPS rainfall data, and soil maps, while socio-cultural data were collected through interviews and participatory mapping conducted with the To Lindu Indigenous Community. All parameters were reclassified into five scoring classes and weighted using AHP based on assessments from three experts. The weighted parameters were subsequently integrated through spatial overlay analysis to generate a zoning index. The results showed that slope had the highest weight (22%), followed by sacred areas (21%), distance from settlements (11%), distance from roads (10%), land cover (9%), distance from rivers and elevation (8% each), soil type (6%), and rainfall (5%). These findings indicate that indigenous socio-cultural values have a level of importance comparable to that of biophysical factors in determining forest management priorities. Based on the zoning index, the 6,473-ha customary forest was classified into four management zones: Core/Protected Zone (1,352.40 ha; 20.89%), Buffer Zone (2,628.25 ha; 40.60%), Limited Utilization Zone (640.91 ha; 9.90%), and Intensive Utilization Zone (1,851.44 ha; 28.60%). The novelty of this study lies in the integration of sacred areas as socio-cultural spatial criteria within a GIS–AHP framework for customary forest zoning. The resulting zoning map provides a practical decision-support tool for indigenous institutions, local governments, and other stakeholders in promoting sustainable customary forest management and spatial planning.